The effect of cocoa certification program in increasing production and farmers income in Tapango Barat Village, Tapango District, Polewali Mandar Regency - Burhanuddin, Burhanuddin; Arsyad, Muhammad; Kurniati, Kurniati; Makmur, Makmur; Indrastuti, Indrastuti (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
The production of Indonesian cocoa beans is significantly increasing but is not in line with its quality. The quality has decreased such as less fermented, not dry, inconsistency of the size & taste. Since then, reputation of Indonesia cocoa beans was considered lower than international standard which caused price is relatively cheap compared to other production countries. The low quality of cocoa beans is due to that the age of cocoa plants in Indonesia is more than 17 years so productivity has declined, besides that cocoa pod borer since 1995 until now has not been eradicated 100%. So, the age of the plant greatly influences the amount of fruit that can be produced. The benefits of cocoa certification program to the farmers production and income are the creation of agribusiness insight and industrial culture in the community, the development of downstream agribusiness subsystem activities in the form of post-harvest, processing and marketing activities which ultimately increase farmers' income and welfare through increased production also will increased foreign exchange earnings for Country. Tapango Barat is a cocoa development center area certified by the Rainforest Alliance (RA) from 2015 until now with the aim of describing the cocoa certification program in Tapango Barat Village, calculating the level of farmers' income and analyzing the effect of the cocoa certification program on increasing farmer production and income. This research was conducted in January – April 2017 using descriptive, income analysis, and multiple regression analysis methods. The results showed that the Mesa Peolo farmer group certified by the Rainforest Alliance (RA) had an income of IDR 17,106,039.073 each year. This shows that the production results from certification program directly influence cocoa farmers’ income.